Cyclo(Phe-Pro) Produced by the Human Pathogen Vibrio vulnificus Inhibits Host Innate Immune Responses through the NF-κB Pathway - Kim, Kiwan (Infect Immun, 2015)
Cyclo(Phe-Pro) (cFP) is a secondary metabolite produced by certain bacteria and fungi. Although recent studies highlight the role of cFP in cell-to-cell communication by bacteria, its role in the context of the host immune response is poorly understood. In this study, we investigated the role of cFP produced by the human pathogen Vibrio vulnificus in the modulation of innate immune responses toward the pathogen. cFP suppressed the production of proinflammatory cytokines, nitric oxide, and reactive oxygen species in a lipopolysaccharide (LPS)-stimulated monocyte/macrophage cell line and in bone marrow-derived macrophages. Specifically, cFP inhibited inhibitory κB (IκB) kinase (IKK) phosphorylation, IκBα degradation, and nuclear factor κB (NF-κB) translocation to the cell nucleus, indicating that cFP affects the NF-κB pathway. We searched for genes that are responsible for cFP production in V. vulnificus and identified VVMO6_03017 as a causative gene. A deletion of VVMO6_03017 diminished cFP production and decreased virulence in subcutaneously inoculated mice. In summary, cFP produced by V. vulnificus actively suppresses the innate immune responses of the host, thereby facilitating its survival and propagation in the host environment.